Keabsahan Akta Notaris Berbasis Dokumen Cyber Notary Ditinjau Dari Asas Tabellionis Officium Fideliter Exercebo - Ni Luh Ari Andini Adnyana; I Nyoman Putu Budiartha; Anak Agung Istri Agung (Fakultas Hukum Universitas Warmadewa, 2024)
In the notarial world, the concept of Cyber Notary has emerged which is currently not fully regulated in law, causing uncertainty among Notaries. In making authentic deeds, Notaries use electronic and non-electronic documents as a legal basis, but there are still doubts regarding the validity of the deeds produced. The principle of Tabellionis Officium Fideliter Exercebo emphasizes notaries to work traditionally, adding to the complexity of the problem. This research aims to The problems are: 1) How is the Regulation of the Use of Cyber Notary Documents in Legislation? 2) How is the validity of deeds made with Cyber Notary documents viewed from the principle of Tabellionis Officium Fideliter Exercebo? The normative legal research method is used, where the ITE Law regulates Cyber Notary, and Permen PSrE regulates the authority of Notary. Cyber Notary documents are considered not to violate the validity of authentic deeds, in line with the principle of Tabellionis Officium Fideliter Exercebo.